Efeitos da ingestão de capsaicina em relação a marcadores de aterosclerose e elucidação das vias de sinalização envolvidas: um efeito TRPV1 dependente - Danielle de Lima Ávila (2019)
Cardiovascular diseases (CVD) are the leading cause of death around the world, and the main triggering factor for these diseases is atherosclerosis. In this context, the search for natural products with antiatherosclerotic activity has become a promising strategy. Among the most consumed natural products worldwide are the peppers, whose main active principle is Capsaicin (Caps). A number of pharmacological properties have been attributed to this compound, among which its anti-inflammatory, antioxidant and anti-lipidic actions stand out. Although widely studied, and that consistent data regarding its atheroprotective role already exists, the signaling pathways involved in Caps' action are unclear, and the data available today are controversial. Some studies relate the effects of Caps to signaling triggered by TRPV1 activation, other studies hypothesize that the action of Caps on foam cells is independent of the activation of their receptor, and may occur by alternative routes, such as those dependent on PPARɤ activity. This work first demonstrated, in vivo, that Caps can attenuate atherosclerosis in ApoE -/- animals, and that this action is probably due to its anti-inflammatory activity. In addition, the action of Caps on the formation of foam cells, a characteristic marker of atherosclerosis, was investigated through in vitro assays using two different macrophage cell lines, such as the RAW 264.7 cell line, which did not express TRPV1, and that of bone marrow derived macrophages (BMDM), which shows expression of this receptor. By comparing the cell profile in the two different strains, it was concluded that, although Caps can act via PPARɤ, in cells with activity of both receptors, the action of Caps is given primarily via TRPV1.